2015
DOI: 10.1007/s11121-015-0595-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Savings Analysis of the Better Beginnings, Better Futures Community-Based Project for Young Children and Their Families: A 10-Year Follow-up

Abstract: This study examined the long-term cost-savings of the Better Beginnings, Better Futures (BBBF) initiative, a community-based early intervention project for young children living in socioeconomically disadvantaged neighborhoods during their transition to primary school. A quasi-experimental, longitudinal two-group design was used to compare costs and outcomes for children and families in three BBBF project neighborhoods (n = 401) and two comparison neighborhoods (n = 225). A cost-savings analysis was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Eight studies (Sanigorski 2008 , de Silva‐Sanigorski 2010 , Fotu 2011 , Kremer 2011 , Utter 2011 , Millar 2011 , Rushton 2015 , Peters 2016 ) were characterized as having used an asset‐based approach in the design and implementation of their intervention as published. All of the studies identified and characterized by the research team as fitting the inclusion criteria for this approach used an approach to build off of existing resources in the community and specifically focused on developing capacity from those assets.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (Sanigorski 2008 , de Silva‐Sanigorski 2010 , Fotu 2011 , Kremer 2011 , Utter 2011 , Millar 2011 , Rushton 2015 , Peters 2016 ) were characterized as having used an asset‐based approach in the design and implementation of their intervention as published. All of the studies identified and characterized by the research team as fitting the inclusion criteria for this approach used an approach to build off of existing resources in the community and specifically focused on developing capacity from those assets.…”
Section: Resultsmentioning
confidence: 99%
“…Generalizable methodologies focus on scientifically rigorous evaluation of complex community change initiatives that enhance their relevance for policy makers and/or funders to extend to other contexts (Amed et al, 2016;Komro et al, 2016;Lee & Chavis, 2012;Peters et al, 2016). Stepped Wedge Cluster Ran dom Control Trials, longitudinal studies with standardized continuous measure ment, interrupted time-series designs, multiple baseline designs, and cost-benefi t analysis were all identified as scientifically rigorous evaluation strategies for CCIs utilizing a range of quantitative data from cluster detection to socio-economic in dicators, asset mapping, and spatial patterning, as well as qualitative data through questionnaires and semi-structured interviews (Kingsley et al, 2014;Komro et al, 2016).…”
Section: Evaluation Methodologiesmentioning
confidence: 99%
“…Positive impacts of Better Beginnings were found for children, their parents, and their communities, relative to comparison communities that did not have Better Beginnings programs, and these persisted until the cohort was 18 years old in Grade 12. A lower percentage of children from Better Beginnings communities had been involved in special education, and they showed higher grades in high school, reported more regular exercise, and fewer reported committing property offences (Peters et al., ). Parents from Better Beginnings communities reported less alcohol consumption, less smoking in the home, had lower levels of clinical depression, and were more involved in their communities than were parents from the comparison communities (Pancer, Nelson, Hasford, & Loomis, ).…”
Section: Better Beginnings Better Futures Knowledge Transfer Initiativementioning
confidence: 99%
“…Also, youth who had participated in Better Beginnings rated their communities as safer and more free from crime than did youth from comparison communities. Economic cost‐savings analysis completed at this stage demonstrated that when the Better Beginnings monetary return to government as a ratio of savings to costs was calculated, for every dollar invested by the government, a return of $2.50 per family was saved (Peters et al., ).…”
Section: Better Beginnings Better Futures Knowledge Transfer Initiativementioning
confidence: 99%